Experimental validation of DNA interactions with nanoparticles derived from metal coupled amphiphiles. Issue 14 (26th October 2018) - Bhar, Rekha; Kaur, Gurpreet; Mehta, S.K.
Abstract : In the present report, a facile strategy for the synthesis of copper nanoparticles utilizing copper@cetylpyridinium chloride as the metal precursor in combination with vitamin C, was been developed. Synthesized nanoparticles (NPs) were well characterized through UV-Vis spectroscopy, dynamic light scattering (DLS), transmission electron microscopy (TEM), Fourier transform infrared (FTIR) spectroscopy, energy dispersive X-ray (EDX) spectroscopy, and powder X-ray diffraction (XRD). The as-obtained NPs were used for binding with deoxyribonucleic acid from calf thymus (CT-DNA). Binding potential of synthesized NPs towards DNA was checked by calculating apparent binding constant and various thermodynamic parameters, like Δ G, Δ H, Δ S and number of binding sites from UV-Vis, circular dichroism, and fluorescence spectroscopy. NPs lead to the change in conformation and mobility of the genomic DNA as notify by the circular dichroism and DNA gel electrophoresis . Synergistic effect of synthesized nanoparticles on DNA was also visualized by the tapping mode atomic force microscopy. Research findings of the present work are expected to have an impact on genomic activities. Abstract :